Darfur / UNAMID Media Brief: 1 (African Press Organisation. Database of Press Releases Related to Africa, 2012)
During a brief visit to El Geneina, West Darfur, the Head of the African Union-United Nations Mission in Darfur (UNAMID) and Joint Chief Mediator a.i, Professor Ibrahim Gambari, met with the Deputy Wali Abul-Gasim Baraka, today to discuss a number of issues including the security situation, development projects and basic services such as education, health care, water and sanitation and infrastructure.